2023
DOI: 10.3390/molecules28041561
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Structural Characterization of Selenium Nanoparticle Composites Modified by Astragalus Polysaccharide and the Cytotoxicity Mechanism on Liver Cancer Cells

Abstract: Astragalus alcohol soluble polysaccharide (AASP) could present superior water solubility and antitumor activity with high concentration. Selenium nanoparticles (SeNPs) have received growing attention in various fields, but their unstable property increases the application difficulties. In the present study, functionalized nano-composites (AASP−SeNPs) were synthesized through SeNPs using AASP (average molecular weight of 2.1 × 103 Da) as a surface modifier, and the preliminary structural characteristics and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…As shown, the cell percentages in the G0/G1 phase and apoptotic rates in solid tumors of CPG-treated mice were obviously increased (p < 0.05) compared with the model group, whereas the proportions in the S phase were remarkably reduced (p < 0.05), which indicated that the growth of S180 tumor cells in vivo was effectively inhibited by CPG-enhanced cellular immune response. These findings provided valuable insights into potential therapeutic strategies for cancer treatment [34].…”
Section: Cell Cycle Distributions and Apoptotic Rates In Tumorsmentioning
confidence: 92%
“…As shown, the cell percentages in the G0/G1 phase and apoptotic rates in solid tumors of CPG-treated mice were obviously increased (p < 0.05) compared with the model group, whereas the proportions in the S phase were remarkably reduced (p < 0.05), which indicated that the growth of S180 tumor cells in vivo was effectively inhibited by CPG-enhanced cellular immune response. These findings provided valuable insights into potential therapeutic strategies for cancer treatment [34].…”
Section: Cell Cycle Distributions and Apoptotic Rates In Tumorsmentioning
confidence: 92%
“…Ji et al. prepared a novel functionalized nanocomposite using alcohol-soluble APS and selenium nanoparticles and found that it was effective in suppressing HepG2 proliferation and accelerating apoptosis by triggering S-phase arrest, thereby stimulating ΔΨm (mitochondrial membrane potential) depletion, increasing the Bax/Bcl-2 ratio, and promoting intracellular reactive oxygen species accumulation ( 127 ). Jiao et al.…”
Section: Anti-tumor Mechanism Of Apsmentioning
confidence: 99%
“…accumulation(127). Jiao et al developed selenium nanoparticles modified with macromolecular weight APS and observed positive results in hepatoma treatment, as indicated by the induction of apoptosis and inhibition of proliferation of HepG2 cells(128).…”
mentioning
confidence: 99%
“…In addition, cytotoxicity against HepG2 is also shown for the SeNPs complex with alcohol-soluble astragalus polysaccharide (AASP) isolated from the stems or dried roots of Astragalus membranaceus , and having biologically active effects [ 99 ]. It is known that AASP can inhibit the growth of solid H22 tumors in mice by increasing the level of serum cytokines (TNF-α, IL-2, and IFN-γ) and the activity of immune cells (macrophages, lymphocytes, and NK cells), therefore inducing apoptosis of tumor cells [ 100 ].…”
Section: The Role Of Nanomedicine In the Treatment Of Liver Pathologi...mentioning
confidence: 99%